The Influence of Gadget use on Early Children's Emotional Development - Riza Yulina Amry; Bety Agustina Rahayu; Anna Nur Hikmawati; Ani Mashunatul Mahmudah (CV. Global Health Science Group, 2023)
Many parents think that gadgets can be easy playmates for children without supervision. But it turns out that excessive use of gadgets will have a negative impact on children's social and emotional development. Seeing this, this study aims to examine the effect of using gadgets on the emotional development of early childhood. This type of research is a non-experimental quantitative research using a correlational research design, namely research that examines the influence between variables. Correlational research aims to reveal the correlative relationship between variables. The approach used in this research is cross sectional. All Littlecare PAUD students. The sampling technique used total sampling and obtained a total of 50 respondents. The research was conducted on Littlecare PAUD students. The measurement instrument uses a questionnaire. Research processing techniques using Microsoft Excel and SPSS. Data analysis used the chi square test. This research will be tested for validity and reliability and has been declared feasible at the STIKES Surya Global Yogyakarta ethical commission with number 3.28/KEPK/SSG/VII/2023. The results of the study show that the majority of children who have positive emotional status are children who have never used gadgets. While the majority of the two negative emotional statuses of children actually sometimes see gadgets. The results of the chi-square test obtained a p-value of 0.000, which means that there is a significant relationship between the use of gadgets and the emotional status of children in Littlecare PAUD.